Assessment of the Severity of Intermediate Coronary Artery Stenosis Using the Systemic Inflammatory Response Index - Akyel, Serdar; Korkmaz, Ahmet; Yıldız, Abdülkadir (MDPI AG, 2025)
Background: Fractional Flow Reserve (FFR) is a method that enables the hemodynamic assessment of coronary artery stenosis. The Systemic Inflammatory Response Index (SIRI) is a new marker calculated by multiplying the neutrophil-to-lymphocyte ratio (NLR) with the monocyte count. It is indicative of the presence and severity of coronary artery disease. This study evaluates the relationship between the functional significance of FFR measurements and the SIRI in intermediate coronary stenosis. Methods: A total of 294 patients with 50–70% stenosis in their coronary arteries based on quantitative measurement following angiography who underwent FFR measurement were included in the study before the FFR procedure. Total and differential leukocyte counts and routine biochemical tests were performed. Results: A total of 37% of the patients were found to have a positive FFR, while 63% had a negative FFR. Significant differences were observed in the neutrophil count, monocyte count, Systemic Inflammation Response Index (SIRI), total cholesterol, and amount of adenosine used between the groups (p < 0.05). A SIRI value of 1.16 was 77% sensitive and 55% specific for FFR positivity. Multivariate logistic regression analysis identified the SIRI as an independent predictor of FFR positivity. Conclusions: Our study has demonstrated that high values of the SIRI may serve as a new biomarker for predicting FFR positivity.
Keywords: Medicine (General); R5-920; fractional flow reserve (FFR); systemic inflammatory response index (SIRI); coronary artery disease; Article